Assessing the Knowlege and Perception Among Breastfeeding Mothers on Covid 19 in Bibiani Anhwiaso Bekwai District - Asiedu, Christiana; Opoku-Danso , Rita; Acquah, Theodora (British Journal of Healthcare and Medical Research, 2022)
Background COVID-19 pandemic has severed the plight of the global citizens. There exists dearth of knowledge among breastfeeding mothers in Ghana during the pandemic. The aim of this study is to investigate the knowledge and perception and how breastfeeding mothers are adhering to Covid 19 protocols in Bibiani Anhwiaso Bekwai districts. Methods A descriptive cross-sectional survey design was adopted. A questionnaire was administered to a sample of 230 mothers. The sample was selected using the multistage sampling procedure. Data was analyzed using descriptive statistics and results presented in frequency tables and percentages. Result It was revealed that breastfeeding mothers had excellent knowledge about COVID-19. The breastfeeding mothers had positive perceptions about breastfeeding during the pandemic but was poorly adherence to the Covid-19 protocols while breastfeeding their children. Conclusion It was therefore recommended that measures must be put in place by health care providers to reinforce adherence of preventive protocols to avert transmission to the virus to the vulnerable children.